An Australian, single‐centre study of surgical management outcomes for early‐stage cervical cancer. (27th July 2020) - Weishaupt, Jennifer; Saidi, Samir; Carter, Jonathan
Abstract : Background: The Laparoscopic Approach to Cervical Cancer (LACC) trial is the first phase III randomised, multicentred trial to compare oncologic outcomes associated with open radical hysterectomy vs minimally invasive surgery (MIS) for treatment of early cervical cancer. Aim: To evaluate our surgical experience in patients with early cervical cancer. Methods and Materials: The Lifehouse Gynaecologic Oncology database was queried based upon the eligibility criteria of the LACC study and included all FIGO 2009 stage (1A1 with lymph vascular space invasion, 1A2, 1B1) cervical cancer women from 2008–2018. Patients were also included in our study if they had abdominal radical trachelectomy (ART), laparoscopic radical hysterectomy (TLRH) and robotic radical trachelectomy (RRT). Results: Forty‐six women were identified with four exclusions. Thirty‐seven women had stage 1B1 disease, 24 had a squamous cell carcinoma, 15 had an adenocarcinoma and three had an adenosquamous carcinoma of the cervix. Of the 42 eligible patients, 32 underwent an open abdominal approach (26 total abdominal radical hysterectomy (TARH), six ART) and ten a MIS approach (nine TLRH and one RRT) with a mean follow‐up of 4.8 years. All 42 women had a pelvic lymph node dissection, eight women had nodal metastases and 16 patients received adjuvant chemoradiation. Two of the nine women in the laparoscopic radical hysterectomy group had a recurrence. Both had adenocarcinoma, stage 1B1 disease. There were no recurrences in the TARH group or radical trachelectomy groups. Conclusion: Our data, albeit limited in number, have reflected the results of the LACC trial that MIS was associated with a lower disease‐free survival than open radical hysterectomy.